WOMEN ENTREPRENEURS WITH PHYSICAL DISABILITIES ECONOMIC EMPOWERMENT: CHALLENGES IN STARTING BUSINESS - Zakaria , Ezarina (International Journal of Psychosocial Rehabilitation, 2020)
This paper will discuss the findings of a study conducted to explore the challenges of women with physical disabilities in entrepreneurship. The scope of the exploration involves the beginning phase of the business that requires informants to relate their experience with the initial business challenges. The study was designed by using a full qualitative approach with data collection using the Focus Group Discussion method. The study area involved four Malaysian zones, namely North, East, Middle, and South. A total of 34 physically disabled women who were an entrepreneur was selected for an interview. The selection of informants was made by selecting recipients of a launched grant from the Malaysian Department of Social Welfare (JKM). Thematic analysis conducted indicated that there were three significant challenges faced by informants during the phase of starting a business: i. lack of access to information, ii. the implications of physical inability, and iii. dual-role challenges. The findings of this study have implications for stakeholders' efforts to increase the achievement of empowering women with physically disabled women in starting a business.Besides, this paper also discusses the academics justification towards the proposal in developing the Economic Empowerment (Entrepreneurship) Model of Women with Physical Disabilitiesas the output of this study.